Coughing Up for Bovine Tb Control - Economic Review of the Proposed National Pest Management Strategy for Bovine Tuberculosis - Peter Clough; Chris Nixon (New Zealand Government, The Treasury, 2000)
This report is a commissioned review of the Animal Health Board's (AHB's) discussion paper Towards a Tb Free New Zealand. The key components of the proposed strategy are: - the goal has shifted from one of management to eradication of bovine Tb; - the annual expenditure requirement over the 10 year life of the proposed strategy doubles over that under the current strategy; - the contribution sought from the Crown and industry more than doubles under the proposed allocation, while that from regional landowners reduces; - the main benefit claimed for the strategy is an avoided risk of trade sanctions in premium markets, plus subsidiary public conservation benefit from possum control. The report evaluates the assertions made by the AHB and concludes that the true risks are likely to be smaller and shorter in duration than the AHB analysis would suggest. Equally, a number of the assertions around the allocation of costs between funding partners are open to alternative interpretations. Consequently NZIER have concluded that the imperative for action in this case may be weaker than for some other biosecurity applications, such as threats of irreversible damage to indigenous biodiversity.
Keywords: 330